Platanus hispanica-inspired design of Co–carbon nanotube frameworks through chemical vapor deposition: a highly integrated hierarchical electrocatalyst for oxygen reduction reactions. Issue 88 (17th October 2016) - Wang, Min-Qiang; Ye, Cui; Bao, Shu-Juan; Chen, Zhao-Yang; Yu, Ya-Nan; Zhang, Yan; Xu, Mao-Wen
Abstract : A novel platanus hispanica-like, metal organic complex derived highly effective ORR electrocatalyst, Co–CNTFs was fabricated in this work. Abstract : In this communication, a novel platanus hispanica-like, highly integrated hierarchical electrocatalyst, with Co–carbon nanotubes anchored through porous Co embedded carbon sphere frameworks (Co–CNTFs), was fabricated using a chemical vapor deposition (CVD) method. More importantly, the prepared Co–CNTFs demonstrate even better activity than commercial Pt electrocatalysts in an alkaline medium. This presented CVD approach provides an effective way to grow metal–CNTs in situ through various metal-complex-derived functional nanomaterials and can be expanded to metallic oxide, metallic sulfide, and metallic phosphide, among others, to introduce carbon nanotube frameworks with a multitude of potential applications.